Similarities and Dissimilarities between Original Institutional Economics and New Institutional Economics. Issue 2 (3rd April 2019) - Spithoven, Antoon
Abstract: Original Institutional Economics and New Institutional Economics display several similarities. However, differences in methodology and normative stance are too big to reconcile both approaches. Both approaches may keep each other sharp.